2009
DOI: 10.1108/13665620910996179
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the best HRM practices‐performance relationship: an empirical approach

Abstract: Purpose -This paper aims to empirically examine the linkages between best human resource (HRM) practices, knowledge management, organisational learning, organisational capabilities and organisational performance. The proposed framework and findings intend to add to the understanding of the specific processes that mediate between best HRM practices and organisational performance. Design/methodology/approach -To carry out this research a survey research strategy was followed. The sample frame for this study cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 121 publications
(138 reference statements)
2
24
0
6
Order By: Relevance
“…The increasing number of empirical research analyzes the effect of various practices of HRM on the organizational performance. Although, regardless of the amount and variety of this research, insufficient consideration has been given to the notion or understanding of which the types of HRM practices affect the organizational performance (Theriou & Chatzoglou, 2009).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…The increasing number of empirical research analyzes the effect of various practices of HRM on the organizational performance. Although, regardless of the amount and variety of this research, insufficient consideration has been given to the notion or understanding of which the types of HRM practices affect the organizational performance (Theriou & Chatzoglou, 2009).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Organization's specific abilities and resources, which are uncommon, valuable, unique, and cannot be replaced, can be organizational competitive advantages and provide a better performance (Barney, 1991;Theriou & Chatzoglou, 2009). Human resources are very crucial resources for organizations.…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognizing that effectively implemented HRM practices will ''cause'' higher performance, it is more important to see ''how'' something is done compared to just ''what'' has been done [64]. Based on the approach that mechanisms of HRM and performance link and clear constituents are vital to more complete perception and knowing of how HRM drives firm performance, different authors [3,19,25,55,60,[65][66][67] describe existing issues using very similar statements ( Table 2). …”
Section: The "Black Box" Problemmentioning
confidence: 99%
“…employee surveys) or techniques (e.g. management by objectives) that contribute to managing human resources in an organisation" (Petersitzke, 2009 Theriou & Chatzoglou, 2009). Previous studies have found mixed results in the relation between HRM practices and employees' turnover intention.…”
Section: Human Resource Management Practices and Turnover Intentionsmentioning
confidence: 99%